(untitled) (Research, Society and Development, 2020)
This study has the objective to evaluate the nutritional state of 4-10-years-old children who attend a certain a public school in Campina Grande, Paraíba, through the parameters of the Body Mass Index (BMI) - also known as Weight-for-Height Index- Weight-for-Age and Height-for-Age Indexes. This paper presents a field research, with descriptive nature and exploratory quality, which has used quantitative methods of research. Its sample was constituted by 33.3% of the population in study, considered sufficiently representative, corresponding to 50 children of both sexes at 4-10 years old, who attend a certain public school. During the data collect, these children were drove to a reserved room at their school, in which the anthropometry took place. The collected data were analysed through the SPSS (Statistical Package for the Social Sciences) database, using the twenty-second version of parameters for Weight-for-Height, Weight-for-Age and Height-for-Age Indexes. Later, its results were interpreted based on the standard scores of growth, previosly mentioned, and compared to the nutritional status table from WHO. It was verified that according to the Height-for-Age parameter, 92% of the children presented proper height for age (n=46), while 8% (n=4) presented low height for age. In relation to the Weight-for-Height parameter, 8% of children presented thinness for height; 40% (n=20) presented eutrophy; and 52% (n=26) of children presented overweight for height. In regard to the Weight-for-Age parameter, 12% (n=7) of children were found underweight for age; 62% (n=31) on proper weight for age; and 24% (n= 12) overweight for age. To measure up the nutritional status of children is extremely important, for it makes possible to evaluate their real nutritional needs for age, as well as their development in a crucial phase in which their mental and physiological maturation happens, along with other many alterations.